What women want: Teaching and learning pronouns in Ngarrindjeri. Issue 4 (2nd October 2021) - Gale, Mary-Anne; Giles, Angela; Simpson, Jane; Amery, Rob; Wilkins, David
ABSTRACT: Ngarrindjeri is one of many Aboriginal languages being actively revived in southern Australia. Women in the Ngarrindjeri community have expressed a desire to speak, read and write their language with the same richness as when it was spoken fluently over 70 years ago. Like many Aboriginal languages, Ngarrindjeri has a rich selection of free and bound pronouns, which express person, number and case, but unlike most other Australian languages, it has a third set of reduced free form pronouns. This tripartite set is used to express discourse saliency and continuing topic, and to definitize noun phrases. This paper addresses the issue of teaching and learning how to use Ngarrindjeri pronouns in traditional ways, but for contemporary purposes. Learning Ngarrindjeri requires understanding grammatical categories such as case that differ substantially from English, plus understanding the use of free forms for discourse saliency, bound forms for continuing topics, and free reduced forms where English uses articles. Finally, it requires memorizing a large number of pronoun forms. We share anecdotes on learning pronouns from individual authors, and a reflection from a young Ngarrindjeri woman. We then propose strategies and resources to make it easier to learn, remember and use the complex, regularized pronoun paradigms of Ngarrindjeri.